PENGARUH KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL DAN KOMITE AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Kurniawan, Elan; Fahrunniza, Iska (Kinerja, 2022)
P This study analyzes the Influence of Independent Commissioners, Institutional Ownership and Audit Committees on the Integrity of Financial Statements in Mining Companies Listed on the Indonesia Stock Exchange in 2016-2020. Multiple linear regression analysis in this research is used to determine the effect of the independent variables, namely the Independent Commissioner, Institutional Ownership and the Audit Committee on the dependent variable, namely the Integrity of Financial Statements. From the population of 158 mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period, using the purposive sampling method, 14 sample companies were obtained and 70 observers passed the criteria. The data used is the annual report of each sample company published through www.idx.co.id. The results showed that the Independent Commissioner had no effect on the Integrity of Financial Statements, Institutional Ownership had no effect on the Integrity of Financial Statements and the Audit Committee had a significant effect on the Integrity of Financial Statements.